Genome-wide association study identifies genetic loci for self-reported habitual sleep duration supported by accelerometer-derived estimates - Hassan S. Dashti (Nature Portfolio, 2019)
Sleep is essential for homeostasis and insufficient or excessive sleep are associated with adverse outcomes. Here, the authors perform GWAS for self-reported habitual sleep duration in adults, supported by accelerometer-derived measures, and identify genetic correlation with psychiatric and metabolic traits